Inventario biológico y estado actual de los arrecifes coralinos a ambos lados del Canal de Panamá - Guzmán, Héctor M (Universidad de Costa Rica, 1994)
A decade ago, several studies conc1uded that the construction of a sea-Ievel canal could have enormous adverse eeological effeets on Panamanian coral reefs. lt was also recognized that the ecological data available were fragmented and poor, suggesting the need to inerease scientifie researeh within the area. Reeent]y. the Panama Canal Commission began considering new altematives to the existing seaway, with two main options: widening the existing canal and locks or building a new sea-level canal. This study presents data on the area, diversity and reeí' structure of aH reefs at both el1trances to the Panama Canal. The total reef area reeorded was 204.6 ha (505.4 acres) and 3.9 ha (9.6 acres) fol' the Caribhean and Paeific, respectively. Forty-eight hermatypie coral species and three hydrocorals were found for the Caribbean Coast, and 14 for lhe Pacifico lo general, al! the reefs in the study area are under "chronic" environmental pressure from heavy sedimentation and oil pollution. The low living coral coverage «6%) and high dertsity of macroalgae (>80%) observed clearly illustrate the intensity, frequency, and diversity of existing impacts in the area. Continued lack of maoagemeot and protection of the coastal resources will affect the natural recovery of the reefs, and the construction of a new canal may increase the pressure 011 the coastal zane, triggering large scale, unpredictable ecological changes in reef communities: